Cross-cultural adaptation, reliability, and validity of the Vertigo symptom scale–short form in the central Kurdish dialect - Zmnako, Sherko Saeed F.; Chalabi, Yousif Ibrahim (Health and quality of life outcomes, 2019)
Background Core vestibular symptoms are vague, hard for patients to describe, and difficult for examiners to quantify. Reliable and validated patient-reported outcome measures (PROMs) have obtained acceptance and popularity in the specialty of vestibular disorders. In Kurdish, there is a critical shortage of such measures. The aim of this survey was to assess the psychometric properties of a central Kurdish version (VSS − SF − CK) of the Vertigo Symptom Scale−Short Form (VSS − SF). Methods The study utilized a regulated process of cross-cultural adaptation to produce the VSS − SF − CK. We examined its psychometric properties by using a cross-sectional survey. Owing to a non-normal distribution, both principal axis factoring and polychoric correlation were used to examine the structure. The internal consistency of the scales was evaluated using Cronbach’s alpha coefficient (α) and composite reliability. The discriminant validity was evaluated using the heterotrait–monotrait ratio of correlations (HTMT .85 ) and the Fornell-Larcker criterion. To assess convergent validity, the instrument was correlated with two comparators. Results The participants ( n = 195) were composed of 165 patients with vestibular symptoms (mean − age 45 ± 15.8, range 61 years; 56.4% women) and 30 healthy participants (mean − age 35 ± 18.6; range 52 years; 60% women). Based on the scree plot, along with other criteria such as Horn’s parallel analysis and minimum average partial, two factors were extracted: vestibular (VSS − V) and autonomic-anxiety (VSS − AA). Both constructs showed a robust structure in terms of adequate loadings and weak cross-loadings. The scales’ αs were 0.81, 0.81, and 0.87 for VSS-V, VSS-AA, and the total scale (VSS − T), respectively. Discriminant validity was established with a value of 0.71 for HTMT (< 0.85). Spearman’s correlation supported the study’s hypotheses and confirmed the convergent validity. Intraclass correlation coefficients revealed high external reliability: test-retest results were 0.93, 0.94, and 0.97 for VSS-V, VSS − AA, and VSS − T, respectively. Conclusion Given a critical shortage in PROMs for the vestibular field, the psychometric properties of VSS − SF − CK were evaluated. The results were promising, as they revealed external consistency and construct validity. The goodness of fit indices showed that the VSS − SF − CK is a reliable and validated PROM that can be used by clinicians and researchers in the Kurdish-speaking population.